Preventing the politicisation of corruption crime law enforcement based on local wisdom - Erma Rusdiana; Nurus Zaman; Lindra Darnela; Uswatun Hasanah (Faculty of Law, University of Muhammadiyah Malang, 2025)
This study focuses on the phenomenon of politicised law enforcement in corruption cases during election years, where legal actions are suspected of being used as political tools to weaken opponents and maintain power. Consequently, law enforcement is perceived as